Maize defense against Spodoptera frugiperda due to landrace genotype and seed treatment - Lima, Andreisa Fabri (2021)
Maize (Zea mays L.) is a commodity of global importance, but its productivity is constantly affected by biotic and abiotic stresses. Aiming to reduce the impacts on productivity caused by insect pests in this crop, the main control methods used are chemical (via spraying or seed treatment) and resistant transgenic cultivars (Bt events), which are mainly used to control fall armyworm, Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae). However, due to recurrent and incorrect use, such measures have not been efficient to control this caterpillar. In addition, seed treatment, as a preventive measure, especially for sucking insects, can alter and compromise plant defenses to other arthropods. Thus, it is important to study the possible effects of seed treatment, as well as other control methods for S. frugiperda in maize. The general objectives of this study were: to evaluate the tolerance levels of six maize genotypes (Amarelão, Aztequinha, Branco Antigo, Palha Roxa, São Pedro and BM 207) under natural infestation of insects, as a promising source for integrated management and for breeding programs (see manuscript 1) and to evaluate the effect of neonicotinoid seed treatment on the constitutive and induced defense of maize plants (see manuscript 2). In the manuscript 1, five maize landrace genotype (Amarelão, Aztequinha, Branco Antigo, Palha Roxa and São Pedro) and a conventional hybrid (BM 207) were used. Under natural infestation of S. frugiperda, plant height, stem diameter and chlorophyll content at two growth stages were evaluated. Tolerance levels to S. frugiperda was calculated, and comparisons between the conventional hybrid and the different landrace genotypes were carried out. Tolerance levels varied depending on the genotype, with Palha Roxa, BM 207, São Pedro and Aztequinha being considered tolerant. Referring to manuscript 2, two maize genotypes (B73 and MC 4050) were used, which seeds were treated with neonicotinoid insecticide (thiamethoxam). In the V4 and V6 growth stages, the effect of seed treatment on the preference and weight gain of S. frugiperda, the levels of phytohormones [salicylic acid (SA) and jasmonic acid (JA)] and constitutive and induced plant volatiles by S. frugiperda caterpillars were evaluated. Plant response to neonicotinoid seed treatment varied as a function of genotype and growth stage. The B73 genotype was the most affected by the neonicotinoid, being observed suppression of SA and volatiles, and a direct effect on the weight gain of S. frugiperda. In conclusion, the landrace genotypes studied have a high tolerance potential, and for this reason should be used in breeding programs aimed at the management of S. frugiperda. Furthermore, thiamethoxam seed treatment is a strategy that should be studied more in depth, as it may influences the defenses of maize plants.